The Differences of Traditional Grammar (Formal Grammar) And Structural Grammar (Notional Grammar) in Language Development - Habib Syukri Nasution (English Teaching and Linguistics Journal (ETLiJ), 2023)
Language is the ‘species-specific’ and ‘species-uniform’ possession of man. It is God’s special gift to mankind. Without language human civilization as we now know it would have remained an impossibility. Language is ubiquitous. Language is a primarily human and non-instinctive method of communicating ideas, emotions and desires by means of a system of voluntarily produced symbols. There were some grammars in language development such as Traditional Grammar, Structural Grammar, Generative Transformational Grammar, Case Grammar, Stratificational Grammar, Tagmemic Grammar, and the last Systemic Functional Grammar. All these grammar gave some contribution for the language development. ThePart of speech, sentence pattern, syntactic structure are some of the contribution of Traditional grammar  and Structural Grammar. Rhetorics, philology and grammar is the first science in the language before linguistics. By the models of grammar, the people can identify the language development especially in scientific of language, begin from Plato and Aristotle era until to day.